The Right to A Healthy Environment: International Law Perspective - Santosa, Mas Achmad (UI Scholars Hub, 2005)
The realization of the damaging impact toward human beings and their quality of life has increased dramatically. This awareness has followed upon very substantial degradation of the world’s environment: land, water, and air, over the past two centuries. While human activity has alaways taken a toll on the natural world, the negative impact of this activity has increased exponentially during this period. This following article describing how we as human beings have a right to live in a healthy environment from the perspective of international law.